Coarse- and Fine-Mesh Space Mapping for EM Optimization Incorporating Mesh Deformation - Feng, Feng; Zhang, Jianan; Zhang, Wei; Zhao, Zhihao; Jin, Jing; Zhang, Qi-Jun (IEEE microwave and wireless components letters, 2019)
Space mapping (SM) is a recognized method for speeding up electromagnetic (EM) optimization. The SM technique often requires an equivalent circuit as the coarse model. In practical cases, equivalent circuit coarse models are not always available. This letter addresses this situation and proposes a new coarse- and fine-mesh SM technique for EM optimization incorporating mesh deformation. By incorporating mesh deformation into coarse-mesh EM optimization, the coarse-mesh EM responses change continuously as the values of the geometrical design variables change. The incorporation of mesh deformation also improves the consistency between the coarse-mesh EM sensitivities and the changes in the coarse-mesh EM responses. This results in the speedup of the coarse-mesh EM optimization and potentially less SM iterations, therefore accelerating the overall SM optimization. This technique is illustrated by two microwave examples.